Zapper! - Clémens, Eric; Musée des Beaux-Arts, Mons (Mons : Centre de Création Artistique de la Ville de Mons, 1988)
Badot, Marco ; Badot-Costello, Catherine ; Charlier, Jacques ; De Lepeleire, Damien ; Duchenne, Philippe ; Flausch, Fernand ; Gomez, Manuel ; Huberlant, Renaud ; Nyst, Jacques-Louis ; Octave, Jean-François ; Pepermans, Albert ; Umbreit, Thierry ; van de Walle, Nathalie ; Van Hoorick, Charles ; Frère, Michel
Zapper!, Musée des Beaux-Arts de Mons, 30 avril - 17 juin 1988
boek